Learning by Erring - Rodríguez Allen, Ana (2003)
Following the Popperian thesis that science begins with problems and using the examples collected by Perelmán to discuss science and technology, I have had the possibility to verify the premises of critical constructivism through my own practice in the classroom over the years. This is the reflection proposed in this article that deals with the variety of reactions that the same example triggers in different audiences.